Novel green automobile brake friction material and preparation method thereof

By using specific formulas and preparation processes in the new green automobile brake friction materials, combining the composite of water-soluble liquid phenolic resin with silicone nanoparticle modified resin, the problem of high noise in new energy vehicles is solved. , material with low noise and high braking performance.

CN119391130APending Publication Date: 2025-02-07NINGGUO FEIYING AUTO SPARE PARTS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411523188.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Traditional braking friction materials in new energy vehicles cannot meet the performance requirements of new green cars for braking friction materials due to their high hardness, brittle texture and high noise.

Method used

A new green automotive brake friction material is adopted, and its formulation includes organic binders, reinforcement material fibers, friction performance regulators, anti-wear lubricants, high temperature inorganic binders, abrasive enhancers and space fillers, through hot pressing and Preparation by pressure-keeping step, combining the composite of water-soluble liquid phenolic resin with silicone nanoparticle modified resin to replace the modified phenolic resin.

Benefits of technology

It reduces the noise of brake friction materials and maintains good braking performance, which is suitable for the needs of new green cars.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a novel green automobile brake friction material and a preparation method thereof. The brake friction material comprises the following components in percentage by weight: 7-9% of an organic binder, 20-30% of reinforcing material fibers, 10-20% of a friction performance regulator, 20-30% of an anti-wear lubricant, 3-7% of a high-temperature inorganic binder, 3-8% of a friction increasing agent and 15-30% of a space filler. According to the invention, the water-soluble liquid phenolic resin and the organic silicon nanoparticle modified resin are compounded under the action of the adhesion promoter, so that the water-soluble liquid phenolic resin with high temperature resistance, salt mist resistance, high flexibility and low hardness replaces the modified phenolic resin in the prior art; the problem that the brake friction material produces loud noise during braking due to the fact that phenolic resin is crisp in texture, poor in flexibility and high in hardness is solved, the obtained brake friction material has excellent brake performance, and compared with a brake material of a traditional fuel vehicle, the noise is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of brake friction material manufacturing, and particularly relates to a novel green automobile brake friction material and a preparation method thereof. Background Art

[0002] my country has proposed the "energy-saving and new energy vehicle" strategy, and the government has paid great attention to the research and development and industrialization of new energy vehicles. New energy vehicles have occupied an increasingly important proportion in the Chinese automobile market due to their low-carbon and environmental protection, high transmission efficiency, intelligent driving and government policy support.

[0003] However, in the field of brake friction pad materials for new energy vehicles, the brake pads of traditional gasoline vehicles cannot meet the requirements of new energy vehicles. The brake pads of traditional gasoline vehicles generate loud noise when braking, which is often masked by the noise of the engine in gasoline vehicles. However, in new energy vehicles, since there is no engine, the noise is extremely low when driving. The friction noise of the brake pads at this time will affect the driver's driving experience; and traditional gasoline vehicles convert mechanical kinetic energy into braking thermal effect when braking. New energy vehicles use a superimposed regenerative braking system to effectively convert the heat generated by braking of traditional gasoline vehicles into electrical energy storage, which brings subversive changes to the wear of brake pads and brake discs. The large inertia, fast acceleration, intelligence and energy recovery functions of new energy vehicles have caused qualitative changes in the application scenarios of traditional friction materials such as braking speed, braking deceleration, braking temperature, braking frequency, etc., coupled with the extremely high requirements of new energy for the NVH of the braking system, making traditional brake friction materials unable to meet the needs of new energy vehicles.

[0004] Patent CN118290067A discloses a high-end ceramic brake pad for new energy vehicles and its preparation method. The pad is prepared by mixing a nitrile-modified phenolic resin with nitrile rubber and other additives through hot pressing and pressure-holding steps. The pad utilizes a copper-free organic friction material formulation, which eliminates copper contamination during use. It also reduces the carbon content in the friction material, improves speed and pressure sensitivity stability, and mitigates thermal decay at high temperatures.

[0005] However, the brake pads made from the nitrile-modified phenolic resin used in this solution are relatively hard and brittle, and generate a lot of noise during braking, which cannot meet the performance requirements of new green cars for brake friction materials. Summary of the Invention

[0006] The purpose of the present invention is to solve the problem of how to reduce the noise generated by the brake friction material during braking while maintaining the braking performance, and to provide a new green automobile brake friction material and a preparation method thereof.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] A new type of green automobile brake friction material, the brake friction material contains the following components in percentage by weight:

[0009] 7-9% organic binder, 20-30% reinforcing material fiber, 10-20% friction performance regulator, 20-30% anti-wear lubricant, 3-7% high-temperature inorganic binder, 3-8% wear enhancer and 15-30% space filler.

[0010] Furthermore, the organic binder comprises the following components by weight: 45-50% of organic silicon nanoparticle modified resin, 40-45% of water-soluble liquid phenolic resin and 5-15% of adhesion promoter.

[0011] Furthermore, the reinforcing material fibers comprise the following components by weight: 50-60% of silane surface-treated composite mineral fibers, 20-40% of AG I reinforcing fibers, 10-25% of calcium sulfate whiskers, and 5-15% of carbon fibers.

[0012] Furthermore, the friction performance regulator comprises the following components by weight: 60-70% friction powder and 30-40% potassium magnesium titanate platelets.

[0013] Furthermore, the anti-wear lubricant comprises the following components by weight: 30-60% of high thermal conductivity graphite, 20-40% of flake graphite, 10-20% of calcined petroleum coke and 5-15% of carbon black.

[0014] Furthermore, the high-temperature inorganic binder comprises the following components by weight: 60-70% antimony sulfide and 30-40% molybdenum disulfide.

[0015] Furthermore, the grinding enhancer comprises the following components by weight: 60-70% zirconium silicate and 30-40% calcined alumina.

[0016] Furthermore, the space filler comprises the following components by weight: 60-80% of calcined barium sulfate and 20-40% of fluorite.

[0017] A method for preparing a novel green automobile brake friction material comprises the following steps:

[0018] Step 1: Weigh the components of the organic binder, reinforcing material fiber, friction performance regulator, anti-wear lubricant, high-temperature inorganic binder, wear enhancer and space filler respectively by weight percentage, and put the weighed formula raw materials into a vertical high-speed mixer for mixing. The mixing time for each group of formula raw materials is 5-6 minutes.

[0019] Step 2: Weigh the components of the formula raw materials by weight percentage and pour them into the hot pressing mold at a hot pressing pressure of 200-300kgf / cm2 The hot pressing temperature is 145-155°C, the air is exhausted every 10-15 seconds, and the air is exhausted 5-7 times in total. The holding time is 540-720 seconds to obtain a brake friction material blank;

[0020] Step 3: Cool the hot-pressed brake friction material blank to room temperature, then heat it to 170-180°C within 4-5 hours, keep it warm for 6-8 hours, stop heating, and wait for the oven temperature to naturally cool to below 50°C to obtain the brake friction material.

[0021] Step 4: The brake friction material is subjected to surface grinding, chamfering, grooving, plastic spraying, labeling, and packaging to obtain a new type of green automobile brake friction material.

[0022] Furthermore, the water-soluble liquid phenolic resin in the organic binder in step 1 is mixed with the organosilicon nanoparticle modified resin and the adhesion promoter by means of atomization spraying with a high-pressure pump.

[0023] Beneficial effects of the present invention:

[0024] The novel green automobile brake friction material prepared by the present invention is prepared by compounding a water-soluble liquid phenolic resin with a resin modified with organic silicon nanoparticles under the action of a viscosity promoter, so that the water-soluble liquid phenolic resin with high temperature resistance, salt spray resistance, high flexibility and low hardness replaces the modified phenolic resin in the prior art, thereby solving the problem of high noise during braking caused by the brittle texture, poor flexibility and high hardness of the phenolic resin. The obtained brake friction material has excellent braking performance and reduces noise compared with the brake materials of traditional fuel vehicles. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.

[0026] Example 1: A new type of green automobile brake friction material, the formula raw materials include the following components: 7kg organic binder, 25kg reinforcing material fiber, 20kg friction performance regulator, 25kg anti-wear lubricant, 3kg high-temperature inorganic binder, 4kg wear enhancer, and 16kg space filler.

[0027] A method for preparing a polyetheretherketone reinforced brake friction material comprises the following steps:

[0028] Step 1: Weigh the components of the organic binder, reinforcing material fiber, friction performance regulator, anti-wear lubricant, high-temperature inorganic binder, wear enhancer and space filler respectively by weight percentage, and put the weighed formula raw materials into a vertical high-speed mixer for mixing. The mixing time for each group of formula raw materials is 5 minutes.

[0029] Step 2: Weigh the components of the formula raw materials by weight percentage and pour them into the hot pressing mold at a hot pressing pressure of 200kgf / cm 2 The hot pressing temperature is 145°C, the air is exhausted every 10 seconds, and there are 5 exhaust times in total. The holding time is 540 seconds to obtain a brake friction material blank.

[0030] Step 3: Cool the hot-pressed brake friction material blank to room temperature, then heat it to 170°C within 4 hours, keep it warm for 6 hours, stop heating, and wait for the oven temperature to naturally cool to below 50°C to obtain the brake friction material.

[0031] Step 4: The brake friction material is subjected to surface grinding, chamfering, grooving, plastic spraying, labeling, and packaging to obtain a new type of green automobile brake friction material.

[0032] The organic binder consists of 3.15 kg of organosilicon nanoparticle modified resin, 3.15 kg of water-soluble liquid phenolic resin and 0.7 kg of adhesion promoter. The water-soluble liquid phenolic resin in the organic binder is mixed with the organosilicon nanoparticle modified resin and adhesion promoter by atomization spraying with a high-pressure pump.

[0033] The reinforcing material fibers consist of 12.5 kg of silane surface-treated composite mineral fibers, 5 kg of AG I reinforcing fibers, 5 kg of calcium sulfate whiskers, and 2.5 kg of carbon fibers.

[0034] The friction performance regulator consists of 12 kg of friction powder and 8 kg of potassium magnesium titanate platelets.

[0035] The anti-wear lubricant consists of 7.5 kg of high thermal conductivity graphite, 10 kg of flake graphite, 5 kg of calcined petroleum coke and 2.5 kg of carbon black.

[0036] The high-temperature inorganic binder consists of 1.8 kg of antimony sulfide and 1.2 kg of molybdenum disulfide.

[0037] The grinding agent consists of 2.4 kg of zirconium silicate and 1.6 kg of calcined alumina.

[0038] The space filler consisted of 9.6 kg of calcined barium sulfate and 6.4 kg of fluorite.

[0039] Example 2: A new type of green automobile brake friction material, the formula raw materials include the following components: 8kg of organic binder, 20kg of reinforcing material fiber, 10kg of friction performance regulator, 26kg of anti-wear lubricant, 5kg of high-temperature inorganic binder, 6kg of wear enhancer, and 25kg of space filler.

[0040] A method for preparing a polyetheretherketone reinforced brake friction material comprises the following steps:

[0041] Step 1: Weigh the components of the organic binder, reinforcing material fiber, friction performance regulator, anti-wear lubricant, high-temperature inorganic binder, wear enhancer and space filler respectively by weight percentage, and put the weighed formula raw materials into a vertical high-speed mixer for mixing. The mixing time for each group of formula raw materials is 5.5 minutes.

[0042] Step 2: Weigh the components of the formula raw materials by weight percentage and pour them into the hot pressing mold at a hot pressing pressure of 250kgf / cm 2 The hot pressing temperature is 150°C, the air is exhausted every 12 seconds, a total of 6 times of exhaust, and the holding time is 630 seconds to obtain a brake friction material blank.

[0043] Step 3: Cool the hot-pressed brake friction material blank to room temperature, then heat it to 175°C within 4-5 hours, keep it warm for 7 hours, stop heating, and wait for the oven temperature to naturally cool to below 50°C to obtain the brake friction material.

[0044] Step 4: The brake friction material is subjected to surface grinding, chamfering, grooving, plastic spraying, labeling, and packaging to obtain a new type of green automobile brake friction material.

[0045] The organic binder is composed of 4 kg of organosilicon nanoparticle modified resin, 3.6 kg of water-soluble liquid phenolic resin and 0.4 kg of adhesion promoter. The water-soluble liquid phenolic resin in the organic binder is mixed with the organosilicon nanoparticle modified resin and adhesion promoter by atomizing and spraying with a high-pressure pump.

[0046] The reinforcing material fibers consist of 12 kg of silane surface-treated composite mineral fibers, 4 kg of AG I reinforcing fibers, 3 kg of calcium sulfate whiskers, and 1 kg of carbon fibers.

[0047] The friction performance regulator consists of 6.5 kg of friction powder and 3.5 kg of potassium magnesium titanate platelets.

[0048] The anti-wear lubricant consists of 13 kg of high thermal conductivity graphite, 7.8 kg of flake graphite, 3.9 kg of calcined petroleum coke and 1.3 kg of carbon black.

[0049] The high-temperature inorganic binder consists of 3.25 kg of antimony sulfide and 1.75 kg of molybdenum disulfide.

[0050] The grinding agent consists of 3.9 kg of zirconium silicate and 2.1 kg of calcined alumina.

[0051] The space filler consisted of 16.25 kg of calcined barium sulfate and 8.75 kg of fluorite.

[0052] Example 3: A new type of green automobile brake friction material, the formula raw materials include the following components: 9kg organic binder, 26kg reinforcing material fiber, 15kg friction performance regulator, 20kg anti-wear lubricant, 7kg high-temperature inorganic binder, 8kg wear enhancer, and 15kg space filler.

[0053] A method for preparing a polyetheretherketone reinforced brake friction material comprises the following steps:

[0054] Step 1: Weigh the components of the organic binder, reinforcing material fiber, friction performance regulator, anti-wear lubricant, high-temperature inorganic binder, wear enhancer and space filler respectively by weight percentage, and put the weighed formula raw materials into a vertical high-speed mixer for mixing. The mixing time for each group of formula raw materials is 6 minutes.

[0055] Step 2: Weigh the components of the formula raw materials by weight percentage and pour them into the hot pressing mold at a hot pressing pressure of 300kgf / cm 2 The hot pressing temperature is 155°C, the air is exhausted every 15 seconds, a total of 7 times of exhaust, and the holding time is 720 seconds to obtain a brake friction material blank.

[0056] Step 3: Cool the hot-pressed brake friction material blank to room temperature, then heat it to 180°C within 5 hours, keep it warm for 8 hours, stop heating, and wait for the oven temperature to naturally cool to below 50°C to obtain the brake friction material.

[0057] Step 4: The brake friction material is subjected to surface grinding, chamfering, grooving, plastic spraying, labeling, and packaging to obtain a new type of green automobile brake friction material.

[0058] The organic binder is composed of 4.05 kg of organosilicon nanoparticle modified resin, 3.6 kg of water-soluble liquid phenolic resin and 1.35 kg of adhesion promoter. The water-soluble liquid phenolic resin in the organic binder is mixed with the organosilicon nanoparticle modified resin and adhesion promoter by atomization spraying with a high-pressure pump.

[0059] The reinforcing material fibers consisted of 14.3 kg of silane surface-treated composite mineral fibers, 7.8 kg of AG I reinforcing fibers, 2.6 kg of calcium sulfate whiskers, and 1.3 kg of carbon fibers.

[0060] The friction performance regulator consists of 10.5 kg of friction powder and 4.5 kg of potassium magnesium titanate platelets.

[0061] The anti-wear lubricant consists of 12 kg of high thermal conductivity graphite, 4 kg of flake graphite, 2 kg of calcined petroleum coke and 2 kg of carbon black.

[0062] The high-temperature inorganic binder consists of 4.9 kg of antimony sulfide and 2.1 kg of molybdenum disulfide.

[0063] The grinding agent consists of 5.6 kg of zirconium silicate and 2.4 kg of calcined alumina.

[0064] The space filler consists of 10.5 kg of calcined barium sulfate and 4.5 kg of fluorite.

[0065] Comparative Example 1: The difference from Example 1 is that a new type of green automobile brake friction material, the formula raw materials contain the following components: 3kg of organic binder, 25kg of reinforcing material fiber, 20kg of friction performance regulator, 25kg of anti-wear lubricant, 3kg of high-temperature inorganic binder, 4kg of wear-increasing agent, and 20kg of space filler.

[0066] The organic binder consists of 1.35 kg of organosilicon nanoparticle modified resin, 1.35 kg of water-soluble liquid phenolic resin and 0.3 kg of adhesion promoter.

[0067] The space filler consists of 12 kg of calcined barium sulfate and 8 kg of fluorite.

[0068] Comparative Example 2: The difference from Example 1 is that a new type of green automobile brake friction material, the formula raw materials contain the following components: 15kg of organic binder, 25kg of reinforcing material fiber, 20kg of friction performance regulator, 20kg of anti-wear lubricant, 3kg of high-temperature inorganic binder, 4kg of wear-increasing agent, and 15kg of space filler.

[0069] The organic binder consists of 6.75 kg of organosilicon nanoparticle modified resin, 6.75 kg of water-soluble liquid phenolic resin and 1.5 kg of adhesion promoter.

[0070] The space filler consists of 9 kg of calcined barium sulfate and 6 kg of fluorite.

[0071] The anti-wear lubricant consists of 6 kg of high thermal conductivity graphite, 8 kg of flake graphite, 4 kg of calcined petroleum coke and 2 kg of carbon black.

[0072] Comparative Example 3: The difference from Example 1 is that the water-soluble liquid phenolic resin in the organic binder is directly mixed with the organosilicon nanoparticle modified resin and the adhesion promoter.

[0073] In the examples and comparative examples, AG I reinforcing fiber was purchased from Zibo Guangcheng High-Tech Materials Co., Ltd. with the brand name GCAG ID. It and other materials were commercially available and are commonly used by people in this field.

[0074] The performance of the new green automotive brake friction materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was tested in accordance with the test standard GB5763-2008. The sample size was 25 cm * 25 cm * 2 cm, the dual material was HT250 / HB200, and the test was performed using an XD-MSM constant speed friction tester with a clamping force of 0.98 MPa. The sample wear rate was tested at 300°C. The total braking percentage of the peak value of the noise generation threshold of the brake friction material was tested in accordance with the standard SAEJ2521-2013. The results are shown in Table 1:

[0075] Table 1

[0076]

[0077] As can be seen from Table 1, Examples 1 to 3 have a lower wear rate, indicating that the new green brake friction material prepared by the present invention has good friction resistance and braking performance, and the noise threshold is extremely low in percentage, which greatly reduces the noise generated by the brake friction material during braking; Comparative Example 1 has less organic binder and insufficient modification of the brake friction material, resulting in poor noise reduction effect, lower bonding between the brake friction materials than Examples 1 to 3, and higher wear rate than Examples 1 to 3; Comparative Example 2 has excessive organic binder content and insufficient friction-resistant material, resulting in reduced friction resistance; Comparative Example 3 has a lower degree of mixing between the water-soluble liquid phenolic resin and the organosilicon nanoparticle modified resin than the mixing method of high-pressure pump atomization spraying, so the dispersion degree of the water-soluble liquid phenolic resin is lower than that of Examples 1 to 3, resulting in lower performance of Comparative Example 3.

[0078] It should be noted that, in this document, relational terms such as first and second, etc., are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "comprises," "comprising," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a list of elements includes not only those elements but also other elements not explicitly listed, or elements inherent to such process, method, article, or apparatus.

[0079] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.

Claims

1. A new type of green automobile brake friction material, characterized in that: The brake friction material contains the following components in weight percentage: 7-9% organic binder, 20-30% reinforcing material fiber, 10-20% friction performance regulator, 20-30% anti-wear lubricant, 3-7% high temperature inorganic binder, 3-8% wear enhancer and 15-30% space filler.

2. A new type of green automobile brake friction material according to claim 1, characterized in that: The organic binder comprises the following components by weight percentage: 45-50% of organic silicon nanoparticle modified resin, 40-45% of water-soluble liquid phenolic resin and 5-15% of adhesion promoter.

3. The novel green automobile brake friction material according to claim 1 is characterized in that: The reinforcing material fiber comprises the following components by weight percentage: 50-60% of composite mineral fiber surface treated with silane, 20-40% of AG I reinforcing fiber, 10-25% of calcium sulfate whisker and 5-15% of carbon fiber.

4. The novel green automobile brake friction material according to claim 1 is characterized in that: The friction performance regulator comprises the following components by weight percentage: 60-70% of friction powder and 30-40% of potassium magnesium titanate platelets.

5. The novel green automobile brake friction material according to claim 1 is characterized in that: The anti-wear lubricant comprises the following components by weight percentage: 30-60% of high thermal conductivity graphite, 20-40% of flake graphite, 10-20% of calcined petroleum coke and 5-15% of carbon black.

6. The novel green automobile brake friction material according to claim 1 is characterized in that: The high-temperature inorganic binder comprises the following components by weight percentage: 60-70% antimony sulfide and 30-40% molybdenum disulfide.

7. The novel green automobile brake friction material according to claim 1 is characterized in that: The grinding enhancer comprises the following components by weight: 60-70% of zirconium silicate and 30-40% of calcined alumina.

8. The novel green automobile brake friction material according to claim 1 is characterized in that: The space filler comprises the following components by weight percentage: 60-80% of calcined barium sulfate and 20-40% of fluorite.

9. The method for preparing a novel green automobile brake friction material according to claim 1, characterized in that: The method comprises the following preparation steps: Step 1: weigh the components of organic binder, reinforcing material fiber, friction performance regulator, anti-wear lubricant, high-temperature inorganic binder, wear enhancer and space filler respectively by weight percentage, and put the weighed formula raw materials into a vertical high-speed mixer for mixing, and the mixing time of each group of formula raw materials is 5-6 minutes; Step 2: Weigh the components of the formula raw materials by weight percentage and pour them into the hot pressing mold. The hot pressing pressure is 200-300kgf / cm 2 The hot pressing temperature is 145-155°C, the air is exhausted once every 10-15s, and the air is exhausted 5-7 times in total. The holding time is 540-720s to obtain a brake friction material blank; Step 3, cooling the hot-pressed brake friction material blank to room temperature, then heating it to 170-180°C within 4-5 hours, keeping it warm for 6-8 hours, stopping heating, and waiting for the oven temperature to naturally cool to below 50°C to obtain the brake friction material; Step 4: The brake friction material is processed by surface grinding, chamfering, grooving, plastic spraying, labeling, and packaging to obtain a new type of green automobile brake friction material.

10. The method for preparing a novel green automobile brake friction material according to claim 9, characterized in that: The water-soluble liquid phenolic resin in the organic binder in step 1 is mixed with the organosilicon nanoparticle modified resin and the adhesion promoter by atomizing and spraying with a high-pressure pump.